Belatacept and regulatory T cells in transplantation: synergistic strategies for immune tolerance and graft survival - Gil-Ran Kim; Kyung-Ho Nam; Je-Min Choi (Clinical Transplantation and Research)
Calcineurin inhibitors (CNIs) have been a cornerstone in solid organ transplantation for many years; however, their prolonged use is linked to significant adverse effects, most notably nephrotoxicity. Belatacept, a modified version of cytotoxic T lymphocyte antigen-4 immunoglobulin with increased binding affinity for its ligand, has emerged as a viable alternative to traditional CNIs due to its lower toxicity profile. Despite these benefits, belatacept is associated with a higher rate of acute rejection, which presents a challenge for long-term graft survival. This review reevaluates the limitations of belatacept in achieving long-term acceptance of transplants and highlights the importance of regulatory T (Treg) cells in maintaining immune tolerance and preventing graft rejection. Additionally, it discusses the potential benefits of combining therapies that boost Treg cells with belatacept to increase the effectiveness of immunosuppression and improve graft outcomes.